SIRT1 (rs3740051) role in pituitary adenoma development - Liutkeviciene, Rasa (BMC Med Genet, 2019)
BACKGROUND: Our purpose was to determine if SIRT1 (rs4746720, rs3740051) genotypes have an influence on the development of pituitary adenoma (PA). METHODS: The study group included 142 patients with pituitary adenoma (PA) and the control group consisted of 826 healthy people. The genotyping of SIRT1 (rs4746720, rs3740051) was carried out using the real-time polymerase chain reaction method. RESULTS: Statistically significant results were obtained in the analysis of SIRT1 rs3740051. Significant differences in genotype (G/G, G/A, A/A) distribution were obtained comparing patients with PA without recurrence and PA with recurrence (0, 17.9, 82.1% vs. 6.7, 6.7, 86.7%, respectively, p = 0.022). Also, statistically significant differences were observed when comparing the genotype (G/G, G/A, A/A) distribution in the non-invasive PA group and the invasive PA group (3.4, 25.9, 70.7% vs. 0, 8.3, 91.7%, respectively, p = 0.003), and allele G was less frequently observed in invasive PA, than in non-invasive PA (4.2% vs. 16.4%, p < 0,001). Further analysis revealed that G/A (OR = 0.261; 95% CI:0.099–0.689; p = 0.007) and each allele A (OR = 0.229; 95% CI:0.091–0.575; p = 0.002) were associated with lower odds of occurring an invasive PA. CONCLUSIONS: Our study revealed that SIRT1 rs3740051 is associated with PA recurrence and invasiveness. The haplotype containing alleles C-A in rs12778366-rs3740051 was found to be associated with increased odds of PA development as well.